Answer: See below
Step-by-step explanation:
Make a table with first set of numbers as 1,3. Multiply both the numbers of this set sequentially by natural numbers to get the following table
1 2 3 4 5 6 7 8 9 10......
3 6 9 12 15 18 21 24 27 30......
We see that in each set of numbers the 2nd number is 3 times the first number.
If we plot these sets of numbers on a graph paper, we get a model depicting all the points which satisfy this ration requirement.
(-2a-4b-6c) - (-a - 2b +3c)
━━━━━━━☆☆━━━━━━━
▹ Answer
-a - 2b - 9c
▹ Step-by-Step Explanation
(-2a - 4b - 6c) - (-a - 2b + 3c)
Remove parentheses
-2a - 4b - 6c - (-a - 2b + 3c)
Collect like terms
-a - 4b - 6c + 2b - 3c
Final Answer
-a - 2b - 9c
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer: -a - 2b -9c
Step-by-step explanation:
-2a - (-a) = -a
-4b - (-2b) = -2b
-6c - (3c) = -9c
-a - 2b - 9c
Identifying the values a, b, and c is the first step in using the Quadratic Formula to find solution(s) to a quadratic equation. What are the values a, b, and c in the following quadratic equation? −3x2 − 5x + 9 = 0 a = 5, b = 9, c = 0 a = 3, b = 5, c = 9 a = −3, b = −5, c = 9 a = −5, b = 9, c = 0
Answer:
a = -3 b = -5 and c = 9
Step-by-step explanation:
−3x^2 − 5x + 9 = 0
The quadratic function is written as
ax^2 + bx+c =0
So a = -3 b = -5 and c = 9
Answer:
a = -3, b = -5 and c = 9
Step-by-step explanation:
Given Quadratic Equation is:
=> [tex]-3x^2-5x+9[/tex]
Comparing it with standard form of quadratic equation [tex]ax^2+bx+c[/tex], we get
=> a = -3, b = -5 and c = 9
An arithmetic sequence has this recursive formula: What is the explicit formula for this sequence? A. an=-6+(n-2)8 B. an=8+(n-6)(-1) C. an=8+(n-1)(-6) D. an=8+(n-1)6
Answer:
an = 8 + (n-1) *(-6)
Step-by-step explanation:
The explicit formula is
an = a1+ d (n-1) where a1 is the initial value and d is the common difference
The initial value is 8 so a1 = 8
The common difference is what we are adding or subtracting each time
We are subtracting 6 each time as we see from the recursive forumla
so d = -6
an = 8 -6(n-1)
or
an = 8 + (n-1) *(-6)
Answer:
C
Step-by-step explanation:
[tex]a_{n}-a_{n-1}=-6\\d=-6\\a_{n}=a_{1}+(n-1)d\\a_{n}=8+(n-1)(-6)[/tex]
What’s the evaluation to 5x(2) + x for x =3
Answer:
48
Step-by-step explanation:
5 x^2 +x
Let x = 3
5 * 3^2 +3
Exponents first
5 * 9+3
Multiply next
45+3
48
Answer:
33
Step-by-step explanation:
If x=3, we have to plug it into 5x(2)+x.
1: Plug it into the equation
(5(3))(2)+3
2: Mutiply it all out
15(2)+3
30+3
33
Hope this helped! :)
Subtract simplify your answer completely
Answer:
Answer is A
Step-by-step explanation:
Answer:
[tex] \frac{3x + 13}{ {x}^{2} + 4x + 5} [/tex]Option A is the correct option
solution,
[tex] \frac{8x + 7}{ {x}^{2} + 4x + 5 } - \frac{5x - 6}{ {x}^{2} + 4x + 5} \\ = \frac{8x + 7 - (5x - 6)}{ {x}^{2} + 4x + 5} \\ = \frac{8x+ 7 - 5x + 6}{ {x}^{2} + 4x + 5 } \\ = \frac{8x - 5x + 7 + 6}{ {x}^{2} + 4x + 5 } \\ = \frac{3x + 13}{ {x}^{2} + 4x + 5 } [/tex]
Hope this helps...
Good luck on your assignment...
Write the following Arithmetic sequence using an Explicit Formula: a1 = 8, an = an-1 -2
Answer:
an = 8 - 2*(n - 1)
Step-by-step explanation:
a1 ; .... ; an-1 ; an
r = an - an-1
r = (an-1 - 2) - an-1
r = an-1 - 2 - an-1
r = -2
So:
an = a1 + r*(n - 1)
an = 8 + (-2)*(n - 1)
an = 8 - 2*(n - 1)
The nth term of the arithmetic sequence using the explicit formula will be [tex]a_{n}[/tex] = 8 - 2(n - 1) thus option (A) is correct.
What is Arithmetic progression?The difference between every two successive terms in a sequence is the same this is known as an arithmetic progression (AP).
The arithmetic progression has wider use in mathematics for example sum of natural numbers.
As per the given,
First term a₁ = 8
[tex]a_{n} =a_{n-1}-2[/tex]
The common difference between the AP will is,
d = [tex]a_{n} -a_{n-1}[/tex]
d = -2
The nth term of an AP is given as a + (n - 1)d
Thus,
[tex]a_{n}[/tex] = 8 + (n - 1)(-2)
[tex]a_{n}[/tex] = 8 - 2(n - 1)
Hence "The nth term of the arithmetic sequence using the explicit formula will be [tex]a_{n}[/tex] = 8 - 2(n - 1)".
For more about Arithmetic progression
https://brainly.com/question/20385181
#SPJ5
Draw the graph of y=4x. From the graph find the value y when x= -2
here is the answer hope this helps
A bakery mixes cookie dough in large batches. For chocolate chip cookies, 10 cups of sugar and 20 cups of flour are needed
Answer:
around 30
Step-by-step explanation: dont quote me though
what is 6-3 plus the square root of 4
Answer:
5
Step-by-step explanation:
6 - 3 = 3
√4 = 2
3 + 2 = 5
Answer:
5
Step-by-step explanation:
6-3 + sqrt(4)
PEMDAS says do the sqrt first
6-3 +2
Then add and subtract
3 +2
5
Please help ASAP
These dogs show hourly earnings for a sample of workers in two different careers
It can be understood from below that Option A for Spread and Option D for Center is the correct answer.
What is Center and Spread ?Center describes a typical value of a data point. Two measures of center are mean and median.
Spread describes the variation of the data. Two measures of spread are range and standard deviation.
In the graph we can see that the hourly earnings are more spread out in Career B and
Career B has greater median hourly earnings than Career A.
Therefore Option A for Spread and Option D for Center is the correct answer.
To know more about Center and Spread
https://brainly.com/question/13027238
#SPJ5
Answer:
A and D
Step-by-step explanation:
Work out the perimeter of a semi circle with radius 3cm give your answer in terms of pi
Answer:
6(π + 1) cm
Step-by-step explanation:
d = 2r
P(s.circle) = πd + d
= π·2·3cm + 2·3cm
= π·6cm + 6cm
= 6(π + 1) cm
(5x - y - 3z) + (3x - 2y - 6z)
━━━━━━━☆☆━━━━━━━
▹ Answer
8x - 3y - 9z
▹ Step-by-Step Explanation
(5x - y - 3z) + (3x - 2y - 6z)
Remove the parentheses
5x - y - 3z + (3x - 2y - 6z)
Collect like terms
8x - y - 3z - 2y - 6z
Final Answer
8x - 3y - 9z
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer: 8x - 3y - 9z
Step-by-step explanation:
(5x - y - 3z) + (3x - 2y - 6z)
Remove Parenthesis
5x - y - 3z + 3x - 2y - 6z
Add Like Terms
8x - 3y - 9z
21%
For all values of x
(2)
f(x) = (x + 2)2 and g(x) = 3(x - 1)
a) Find gf(x), giving your answer in the form a(x2 + bx + c)
where a, b and care integers.
(x² +
x +
b) Find g '(12)
(2)
Answer:
f(x) = (x + 2)2 = 2x + 4
g(x) = 3(x - 1) = 3x - 3
gf(x) = (2x + 4)(3x - 3)
= 6x² - 6x + 12x - 12
= 6x² + 6x - 12
To write the final answer in the form
a(x² + bx + c) we factorize the expression
Thus
6x² + 6x - 12
= 6( x² + x - 2)
where a = 6, b = 1 and c = - 2
b.) to find g '(12) we first find g ′
To find g′ equate g(x) to y
Thus
g(x) = y
y = 3x - 3
x = 3y - 3
3y = x + 3
Divide both sides by 3
We get
y = x+3/3
That's g′ = x + 3 / 3
g′(12) = 12 + 3 / 3
= 15/3
= 5
Hope this helps
Please help i will mark brainliest!
Answer:
B and C are the answers
Step-by-step explanation:
What are the chances of choosing a black marker out of a bag containing 3 red markers, 5 blue markers, 3 yellow markers, and 4 black markers? What is the probability of choosing two black markers if the first marker is put back before the second is drawn?
Answer:
[tex]\dfrac{16}{225}[/tex].
Step-by-step explanation:
It is given that,
Number of red markers = 3
Number of blue markers = 5
Number of yellow markers = 3
Number of black markers = 4
Total markers = 3 + 5 + 3 + 4 = 15
Probability of getting a black marker is
[tex]P(Black)=\dfrac{\text{Number of black markers}}{\text{Total markers}}[/tex]
[tex]P(Black)=\dfrac{4}{15}[/tex]
Probability of choosing two black markers if the first marker is put back before the second is drawn, is
Required probability [tex]=P(Black)\times P(Black)[/tex]
[tex]=\dfrac{4}{15}\times \dfrac{4}{15}[/tex]
[tex]=\dfrac{16}{225}[/tex]
Therefore, the probability of choosing two black markers if the first marker is put back before the second is drawn, is [tex]\dfrac{16}{225}[/tex].
Can someone please help me graph these 4?
Answer:
These are ordered 1, 2, 3, 4
For each of the sequence below identify whether there is a common ratio. If there is identity what it is. If there is not a common ratio type none.
yes
1.-3
2.3
3.10
4.2
5.3
Barika, Akeelah, and James raised $76.23 for their dance team. James raised twice as much as Barika, who earned 2.60 less than Akeelah. If x = the amount raised by Akeelah, choose the expressions that represent the amount each other player raised. x – 2.60 2x + 5.20 .5x + 2.60 2x – 5.20
The amount raised by Akeelah is x, by Barika is x- 2.60, and by James is 2x- 5.20.
If we analyze it via steps,
We first take the value we know, that is the amount raised by Akeelah that is x. So if Barika is 2.60 less than Akeelah we will numerically express the equation as x-2.60.
Then we look at the amount raised by James it says that it is twice as much as Barika, we numerically express that as
2(x- 2.60) = (2.x) - (2 . 2.60) = 2x -5.20 (simpler form)
If we want to find out the amount we can even do so by adding the amount raised by Barika, Akeelah, and James. We numerically express that as x + (x-2.60) + (2x-5.20) . This equation will be equal to the total value given as the amount raised by all three which is $76.23.
So, By the Problem,
x + (x-2.60) + (2x-5.20) = 76.23
=> 4x - 7.80 = 76.23
=> 4x = 68.43
=> x = 68.43/4
=> x = 17.11
Therefore, Akeelah raised x = $17.11
Barika raised x-2.60 = $14.51
James raised 2x -5.20 = $29.02
Learn more about algebra:
https://brainly.com/question/30166597
Amy works for 36 hours per week for 10 weeks during the summer, making $\$3000$. If she works for 30 weeks during the school year at the same rate of pay and needs to make another $\$3000$, how many hours per week must she work?
Answer:
12 hours
Step-by-step explanation:
$3000 / 36hours / 10weeks = $8.33333333333
$3000 / 30weeks / $8.33333333333 = 12hours
Answer:
12
Step-by-step explanation:
Since she only needs to make the same amount of money, if she works for 3 times as many weeks, she can work 3 times fewer hours per week, meaning she can work 1/6x36= 12 hours per week
What must be subtracted from 4x4 - 2x3 -6x2 + x - 5 so that the result is exactly divisible by 2x2 + 3x - 2 ?
Simplify the given expression. 2x^2-2/x/2(x^2+9)/16x^2-29x
Answer:
work is shown and pictured
what is 2 Square of 100? what is 3 Square of 250
Answer:
10,000
15,625,000
Step-by-step explanation:
Squaring a number means multiplying a number by itself.
100^2=100*100=10,000
Cubing a number means multiplying a number by itself 3 times.
250^3=250*250*250=15,625,000
Hope this helps ;) ❤❤❤
Answer:
10000
15,625,000
Step-by-step explanation:
100 x 100 = 10000
250 x 250 x 250 = 15,625,000
Apply this definition and the properties of exponents to represent the expression 7 3/4 in radical form
Step-by-step explanation:
7^3/4=
[tex] \sqrt[4]{7 {}^{3 \\} } [/tex]
=
[tex] \sqrt[4]{343} [/tex]
A rider sits on a motorcycle. The motorcycle has a mass of 237 kilograms.The rider has a mass of 89 kilograms. What is the total mass of the motorcycle and the rider????
Answer:
326 kg
Step-by-step explanation: weight of the motorcycle: 237 kg
Mass of the rider: 89 kg
Total mass: 237+89:326 kg
Answer:
326 kg
Step-by-step explanation:
tbh im lazy to type it in i owe u a explanation
You are selling decorative eggs for your club.
Medium Eggs sold for $3 each. Large Eggs sold for
$6 each. A total of 190 Eggs were sold, and sales
totaled $870. How many Large Eggs did you sell?
Sarah dreams of going to medical school and giving quality medical care to people who live in countries in crisis. Which of the following is an organization she might want to work for? Peace Corps. World Health Organization. United Nations. Alliance for small island states
I would say World Health Organization because that is for the world and Sally dreams of going to medical school and giving quality medical care to people who live in countries in crisis.
Answer:
B
Step-by-step explanation:
I took the test ;P
Here is a list of ingredients to make biscuits.
200 g butter
180 g caster sugar
400 g plain flour
20g chocolate chips
Andrew only has 300 g of plain flour.
How much of the other ingredients should he use?
g butter
g caster sugar
Help due tomorrow and I'm a bit thick and tired
g chocolate chips
Answer:
[tex]\frac{200}{1} * \frac{3}{4} = 150g[/tex] < butter
[tex]\frac{180}{1}*\frac{3}{4} = 135g[/tex] < castor sugar
[tex]\frac{20}{1}*\frac{3}{4} = 15g[/tex] < chocolate chips
full working out :)
Which of the following is the complete factorization of the polynomial below
x3 + x2 - 17x+15
Answer:
[tex]\boxed{\sf \ \ \ (x-1)(x-3)(x+5) \ \ \ }[/tex]
Step-by-step explanation:
Hello,
1 is a trivial zero so we can write
[tex]x^3+x^2-17x+15=(x-1)(x^2+2x-15) = (x-1)(x^2+5x-3x-15)\\==(x-1)(x(x+5)-3(x+5))=(x-1)(x-3)(x+5)[/tex]
hope this helps
What is the x-intercept of y=x^2+6x-8
Answer:
(4,0) , (2,0)
Step-by-step explanation:
To find the x-intercept, substitute in
0
for
y
and solve for
x
. To find the y-intercept, substitute in
0
for
x
and solve for
y
The perimeter of an equilateral triangle must be at most 57 feet. Create an inequality to find
what the length of the sides should be. Solve the inequality by showing all of your work.
We know that the perimeter is at most 57 feet. We will call the length of each side with the variable 'x'. Each side is the same since it's an equilateral triangle.
The perimeter of the triangle is defined as '3x' because 3 times the side length of an equilateral triangle is its perimeter.
Since the perimeter is at most 57 feet, it can't be more than that. Therefore, we get the inequality 3x≤57.
This inequality is the same as saying the perimeter is less than or equal to 57 feet.
Now we solve.
3x≤57
Isolate 'x': 3x/3≤57/3
0<x≤19 is our answer.
The reason there is a "0<" added is because the side of a triangle can't be less than 0, that would be impossible.